"El pájaro de cuatro notas": the reception of Argentine women writers and artists' work in avant-garde magazines (1920–1930). Issue 3 (2nd September 2017) - Sutherland, Camilla
Abstract: This article assesses the reception of Argentine women writers and artists' work within vanguard magazines. Taking as case studies the work of Norah Lange and Norah Borges, I identify four key tropes that emerge in reviews of their creative output published between 1920 and 1930. This article brings to light original archival material in order to expose how women's peripheral position in the artistic sphere of early twentieth-century Latin America was enacted at a discursive level. In so doing, I propose that the gendered dynamics evident within avant-garde magazines represent a microcosm of women's experiences within the vanguard more broadly. This article aims to contribute to a thorough investigation into how marginalisation is enacted and enforced, exposing the extra-literary processes which construct an artistic sphere that is inhospitable to women practitioners.